PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN IBU DALAM PEMBERIAN MP-ASI ANAK USIA 6-24 BULAN DI PUSKESMAS BAKKAL GAJAH - Sihombing, Ulibasa Agustina; Wahyu, Afnijar (Indonesian Trust Nursing Journal, 2023)
Breast milk companion feeding begins after the baby is 6 months old. Until the age of 6 months, the baby can simply get food intake from breast milk without the addition of other foods or drinks. Untimely feeding of companion feeding can cause disruption to the growth and development of the baby. One of them is the provision of early in East Java in 2015 which is still high at 69.28%. The purpose of this study is to find out the influence of health education on maternal knowledge in the provision of Breast milk companion feeding in children aged 6-24 months at the Bakal Gajah Health Center in 2021. This study uses the design of one group pre and posttest design. The population in this study was mothers who had children aged 6-24 months at The Bakal Gajah Health Center. Sampling technique is purposive sampling. The number of samples in this study was 47 respondents. The data was collected using questionnaires. The data will be analyzed using univariate and bivariate analysis with Wilcoxon test. Wilcoxon test results obtained a value of sig=,000. There is an influence on the provision of health education on maternal knowledge in the provision of children aged 6-24 months at the Bakkal Gajah Health Center in 2021. Abstrak Pemberian makanan pendamping ASI (MP-ASI) mulai dilakukan setelah bayi berumur 6 bulan. Sampai usia 6 bulan, bayi cukup mendapatkan asupan makanan dari ASI tanpa ditambah makanan atau minuman lain. Pemberian makanan pendamping yang tidak tepat waktu dapat menyebabkan gangguan pada pertumbuhan dan perkembangan bayi. Salah satunya pemberian MP-ASI dini di Jawa Timur tahun 2015 yang masih tinggi yaitu 69,28%. Tujuan penelitian ini untuk mengetahui pengaruh pendidikan kesehatan terhadap pengetahuan ibu dalam pemberian MP-ASI pada anak usia 6-24 bulan di Puskesmas Bakal Gajah Tahun 2021. Penelitian ini menggunakan rancangan one group pre dan posttest design. Populasi dalam penelitian ini adalah ibu yang mempunyai anak usia 6-24 bulan di Puskesmas Bakal Gajah. Teknik pengambilan sampel yaitu purposive sampling. Jumlah sampel dalam penelitian ini adalah 47 responden. Data dikumpulkan menggunakan kuesioner. Data akan dianalisis menggunakan analisis univariat dan bivariat dengan uji Wilcoxon. Hasil uji Wilcoxon diperoleh nilai sig=,000. Ada pengaruh pemberian pendidikan kesehatan terhadap pengetahuan ibu dalam pemberian MP-ASI anak usia 6-24 bulan di Puskesmas Bakal Gajah Tahun 2021.